2014
DOI: 10.1063/1.4860395
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stability of molten 2,4,6-trinitrotoluene at high pressure

Abstract: 2,4,6-trinitrotoluene (TNT) is a molecular explosive that exhibits chemical stability in the molten phase at ambient pressure. A combination of visual, spectroscopic, and structural (x-ray diffraction) methods coupled to high pressure, resistively heated diamond anvil cells was used to determine the melt and decomposition boundaries to >15 GPa. The chemical stability of molten TNT was found to be limited, existing in a small domain of pressure-temperature conditions below 2 GPa. Decomposition dominates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Unlike at ambient pressure, the difference in the melting and the decomposition temperatures narrowed at high pressures, and TNT was found to decompose rather than melt when heated under pressures above 6 GPa. 60 This is similar to other explosives such as HMX and PETN.…”
Section: Phase Transitions In Some Importantsupporting
confidence: 66%
See 2 more Smart Citations
“…Unlike at ambient pressure, the difference in the melting and the decomposition temperatures narrowed at high pressures, and TNT was found to decompose rather than melt when heated under pressures above 6 GPa. 60 This is similar to other explosives such as HMX and PETN.…”
Section: Phase Transitions In Some Importantsupporting
confidence: 66%
“…Dattelbaum et al carried out a detailed study of the high-pressure melting line and chemical stability of molten TNT in a resistively heated diamond anvil cell (DAC), and their studies have shown a steep melt boundary of 61 K/GPa up to 2 GPa (Figure ). Unlike at ambient pressure, the difference in the melting and the decomposition temperatures narrowed at high pressures, and TNT was found to decompose rather than melt when heated under pressures above 6 GPa . This is similar to other explosives such as HMX and PETN.…”
Section: Phase Transitions In Some Important Secondary Explosivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was impossible to determine whether the two points at higher pressure (where agreement with our EOS is not as good) were melted, chemically decomposed, or some combination. 28 As has been noted, 28 the melt line is quite steep (∼80 K/GPa). At this point we reiterate that this is the melt line of pure TNT, and that its precise relation to constitutive properties of Comp B is not straightforward.…”
Section: Resultsmentioning
confidence: 77%
“…The combination of our EOS predict von Neumann spike and CJ pressures of 40.1 GPa and 28.9 GPa, respectively. The TNT melt line was recently measured to high accuracy by Dattelbaum, et al 28 We compare these data with 95500 results in Figure 3. Once again we find good agreement, particularly at lower pressures.…”
Section: Resultsmentioning
confidence: 81%